Cellulose nanocrystals (CNC) reinforced shape memory polyurethane ribbons for future biomedical applications and design. (March 2020) - Garces, Irina T; Aslanzadeh, Samira; Boluk, Yaman; Ayranci, Cagri
Shape memory materials are an innovative type of materials that reversibly store a temporary shape and recover back to the original dimensions with the application of an external mechanism such as heat. Shape memory polymers (SMP), specifically thermoplastic SMP (e.g. shape memory polyurethane (SMPU)) have received much attention during the past decade because of the promising future applications and advantages such as ease of processability for thermoplastic SMP (e.g. by 3-D printing), cost, and biocompatibility. In the biomedical field, applications such as stents, surgical sutures, and orthodontic devices, amongst others have been proposed. The addition of fillers to the material can modify the material to improve their load bearing capabilities. Bio-based fillers such as cellulose nanocrystals (CNC) have been proposed in a variety of reinforcing applications. The present work focuses on the experimental description of the addition of nonmodified CNC to SMPU. The work studied the effect on melt-extruded ribbons, for 0, 0.5, 1, 2, and 4 wt%. An increase of yield point, toughness, flexural modulus, recovery rate, and decrease of total time showed that SMPU/CNC nanocomposites are a potential candidate to use in future biomedical applications.